Media: The Existence Based on Senior High School Students' Perspective in Physics Learning - Ziola Natasya; Intan Purnama Yani; Suriza Putri; Desnita, Desnita; Usmeldi, Usmeldi (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
TThe COVID-19 pandemic, Industrial Revolution 4.0, and Society 5.0 have caused significant changes in various aspects of life, including education. This research aims to determine what media are used in physics learning, what kind of media students like and need in implementing physics learning. This quantitative descriptive research describes the existence of media in physics learning based on the answers of respondents consisting of 54 high school students in the city of Padang. The research instrument employed is a Google Form questionnaire validated by experts in learning media development. The media most often used in physics learning is the whiteboard, while the media least frequently used is the virtual laboratory. The media that is most popular with students in learning physics is experimental tools, while the media that is least popular is the whiteboard. The media that students need most in learning physics are experimental tools, while tutorial videos are the ones that are least needed. The results of this research can be used as a reference for schools in developing learning media that suit the needs of students and teachers.